2001
DOI: 10.1007/s004210100484
|View full text |Cite
|
Sign up to set email alerts
|

Human body surface area: measurement and prediction using three dimensional body scans

Abstract: The development of three dimensional laser scanning technology and sophisticated graphics editing software have allowed an alternative and potentially more accurate determination of body surface area (BSA). Raw whole-body scans of 641 adults (395 men and 246 women) were obtained from the anthropometric data base of the Civilian American and European Surface Anthropometry Resource project. Following surface restoration of the scans (i.e. patching and smoothing), BSA was calculated. A representative subset of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
122
0
3

Year Published

2002
2002
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 188 publications
(131 citation statements)
references
References 5 publications
6
122
0
3
Order By: Relevance
“…For instance, DuBois (1914) and Mehra (1959) reported that %RBSA for the head & neck had a mean of 6% BSA, while the %RBSA amounts to approximately 9ϳ10% BSA according to Niya (1931), Kurazumi (1994) and the present study. For the trunk, Niya (1931) obtained %RBSA by 25%, 32% for Tikuisis et al (2001) and Mehra (1958), and 35ϳ38% for US EPA (1985) and the present study. The one conceivable reason that those studies showed differences may result from the varieties between races.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…For instance, DuBois (1914) and Mehra (1959) reported that %RBSA for the head & neck had a mean of 6% BSA, while the %RBSA amounts to approximately 9ϳ10% BSA according to Niya (1931), Kurazumi (1994) and the present study. For the trunk, Niya (1931) obtained %RBSA by 25%, 32% for Tikuisis et al (2001) and Mehra (1958), and 35ϳ38% for US EPA (1985) and the present study. The one conceivable reason that those studies showed differences may result from the varieties between races.…”
Section: Discussionsupporting
confidence: 64%
“…DuBois, 1914;Hakumi, 1943;Mehra, 1958;Kurazumi, 1994;Tikuisis et al, 2001). However, there are some discrepancies in %RBSA among studies.…”
Section: Discussionmentioning
confidence: 99%
“…The case study demonstrates that scanning can be effective when scanning inanimate objects, because concerns over involuntary movement are diminished. This method is supported by Tikuisis et al (2001), who reported highly accurate resolution of scanned hand data. Based on the conclusion of Surendran et al (2009), Plaster of Paris would be a very effective material for scanning, due to its matte appearance, even colour tone, opacity and its ability to capture fine detail, but casting can be messy, time consuming and may be uncomfortable for patients.…”
Section: Figure 1(a): Polygonal Mesh From Direct 3d Laser Scanningmentioning
confidence: 72%
“…The interested disciplines are orthopedics (Ono, 1995;Hackenberg et al, 2000), orthodontics (Motegi et al, 1996;Hoeflinger, 1996), physiology (Tikuisis et al, 2001), plastic surgery (Okada, 2001) and biomechanics (Ronsky et al, 1999;Savatier et al, 2001). The common characteristic of the existing techniques applied in medical applications is the required high accuracy.…”
Section: Introductionmentioning
confidence: 99%
“…Laser scanning Okada, 2001;Tikuisis et al, 2001) and structured light methods (Wolf, 1996;Hackenberg et al, 2000;Sitnik and Kujawinska, 2000) are widely used to measure objects in macro scale. They have common characteristics in the acquisition and processing.…”
Section: Introductionmentioning
confidence: 99%